COMPETITIVE ADVANTAGE MITRA KELUARGA HOSPITAL SURABAYA THROUGH DIFFERENTIATION AND EFFICIENCY - Susanto, Adi (Research In Management and Accounting (RIMA), 2019)
Growth and the high competition in the hospital business, demands the existence of an appropriate strategy to achieve competitive advantage. Strategies that can be used is a strategy of differentiation through efficiency and co-branding and green health care in building competitive advantage to achieve sustainable business growth. The strategy of differentiation can be made through product differentiation, service, human resources, product and image channels. Differentiation strategy and the efficiency of performed detailed analysis using SWOT analysis, Resource Based View (RBV) and carried out in a comprehensive manner through the assessment method of the Balanced Scorecard (BSC), which measures the performance of companies from both the financial and non financial perspective as a whole, so that it can be produced more precise measurement of the indicators for the survival and growth of the company. This thesis research done through qualitative approach on RS. Mitra Keluarga Surabaya on an ongoing basis to evaluate the strategy of differentiation and efficiency at the same time, to be able to always increase sales growth and get the value of an optimal efficiency in the operating costs of the hospital.